Occupational asthma due to methyl methacrylate and cyanoacrylates. Issue 11 (November 1985) - Lozewicz, S; Davison, A G; Hopkirk, A; Burge, P S; Boldy, D A; Riordan, J F; McGivern, D V; Platts, B W; Davies, D; Newman Taylor, A J
Abstract : Five patients had asthma provoked by cyanoacrylates and one by methyl methacrylate, possibly because of the development of a specific hypersensitivity response. Acrylates have wide domestic as well as industrial uses, and inhalation of vapour emitted during their use can cause asthma.